Analytical models for estimation of the maximum strain of beam structures based on optical fiber Bragg grating sensors - Choi, Se Woon; Lee, Jihoon; Oh, Byung Kwan; Park, Hyo Seon (Journal of Civil Engineering and Management, 2015)
The structural safety of a beam structure is assessed by a comparison between the maximum stress measured during monitoring and the allowable stress of the beam. However, the strain directly measured from a fiber Bragg grat- ing (FBG) strain sensor may not be identical with the actual maximum strain induced in the structural member. Unless a FBG strain sensor is installed exactly on where maximum strain occurs, the reliability of the evaluated safety based on the measured strain depends on the number and location of sensors. Therefore, in this paper, analytical models are presented for estimation of the maximum values of strains in a linear elastic beam using the local strains measured from FBG sensors. The model is tested in an experiment by comparing estimated maximum strain from FBG sensors and directly measured strain from electrical gages. For the assessment of safety of typical beam structures in buildings and infrastructures, analytical models for various loading and boundary conditions are provided.